Visions and cognitive awareness to achieve aesthetic pleasure in the pictorial heritage of Muslims (A psychological aesthetic reading ( - Khudhair Jasim Rashid (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The research tagged (Visions and Cognitive Perception to Achieving Aesthetic Pleasure in the Pictorial Heritage of Muslims _ A Psychological Aesthetic Reading) has shed light on the pictorial inheritance left by Muslims that is still the fruit of meditation and visions to achieve aesthetic pleasure in accordance with the requirements of its achievement, which are painted in an Islamic semi-sanctified tint. Thus, he accomplished a unique cultural and artistic inheritance in terms of aesthetics and knowledge, beyond the limits of sensory work to consolidate aesthetic pleasure. It covered the walls of palaces, filled the pages of manuscripts, and beautified it with ceramics. This prompted the two researchers to set out to discover the brilliance of visions and cognitive awareness in the resurgence of aesthetic pleasure that revolves in its orbit of photography among Muslims. Thus, it occupied its place among the international arts, according to its artistic characteristics that distinguish it in the presence of features that stimulate the achievement of aesthetic pleasure. The problem has been identified by the question: What is the mechanism for Muslims to operate visions and cognitive perception in photography in achieving aesthetic pleasure? It was followed by the importance and goal, defined terminology, and defined language and terminology. As for the intellectual framework, it dealt with (imaging among Muslims. A conceptual view), then it dealt with (aesthetic visions and the realization of pleasure) and then (cognitive perception and understanding the artistic work). The researchers reached a number of results, including: It showed the work of Islamic photography in enriching a conceptual framework for creative advantage with aesthetic and cognitive visions in achieving pleasure.